ALIH AKSARA DAN ALIH BAHASA TEKS SYAIR BINTARA MAHMUD SETIA RAJA - Andani, Rike; Hasanuddin WS, Hasanuddin WS (Jurnal Bahasa dan Sastra, 2019)
This study aims to: (a) present the physical description form of the Syair Bintara Mahmud Setia Raja manuscript; (b) presents the form of the transcription of the text of Syair Bintara Mahmud Setia Raja in the text of the Syair Bintara Mahmud Setia Raja; (c) presents the form of the translation of the text of the Syair Bintara Mahmud Setia Raja text in the Syair Bintara Mahmud Setia Raja manuscript. This research includes philology research. This research resulted in (1) description of Syair Bintara Mahmud Setia Raja manuscript; (2) the transfer of Syair Bintara Mahmud Setia Raja's text which is transcribed from Arabic-Malay script to Latin script; (3) the transfer of the text of the Syair Bintara Mahmud Setia Raja text which was translated from Malay into Indonesian.